Обработка информации в Интернет-системе экспертных оценок на этапе комплектования (Библиосфера, 2010)
Implementation of the software in the acquisition technology at the Central Library System of the RAS Library on natural sciences allows to analyze the experts' estimations using the graphic data presentation. It considerably makes easier for the acquisition librarians to select publications which are of most interest to the scientists and employees of the RAS. The structural-functional scheme for the automated working place of an acquisition librarian and its working algorithm are presented.